1980
DOI: 10.1073/pnas.77.7.4349
|View full text |Cite
|
Sign up to set email alerts
|

Isoprotein specificity in the hepatic uptake of apolipoprotein E and the pathogenesis of familial dysbetalipoproteinemia.

Abstract: The uptake and catabolism of lamellar complexes of rat 12MI4abeled apolipoprotein (apo) E with egg lecithin were increased severalfold in perfused livers of rats given large amounts of 17a-ethynylestradiol for 5 days. Estrogen-stimulated uptake of lamellar complexes of human apo E that contained al of the major normally occurring "isoforms" of the protein (apo E-1, E-2, E-3, and E4) was comparable to that of rat apo E. By contrast, uptake of complexes containing apo E from individuals with familial dysbetalipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(59 citation statements)
references
References 29 publications
4
54
0
1
Order By: Relevance
“…In the present study, however, no difference was observed between the males and females subjects for apolipoprotein A-I. The apolipoprotein E level was higher in the females than in the males in all age groups above 10 years, and this result is in agreement with that reported by Havel et al [20] ; it seems of great significance that the results obtained by Havel et al could be confirmed in the present study for each of the age groups. Apolipoproteins A-I and A-II, B, and C-II and C-III are, respectively, the principal proteins of HDL, LDL, and TG-rich lipoprotein, and apolipoprotein E is thought to be deeply involved in the metabolism of cholesterol.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, however, no difference was observed between the males and females subjects for apolipoprotein A-I. The apolipoprotein E level was higher in the females than in the males in all age groups above 10 years, and this result is in agreement with that reported by Havel et al [20] ; it seems of great significance that the results obtained by Havel et al could be confirmed in the present study for each of the age groups. Apolipoproteins A-I and A-II, B, and C-II and C-III are, respectively, the principal proteins of HDL, LDL, and TG-rich lipoprotein, and apolipoprotein E is thought to be deeply involved in the metabolism of cholesterol.…”
Section: Discussionsupporting
confidence: 82%
“…Every individual arterial lesion was classified accordingly. Within a group the total number of both mild lesions (categories [1][2][3] and moderate plus severe lesions (categories 4 and 5) of all mice was counted. After dividing the total number of lesions (mild and moderate plus severe, separately) by the number of mice per group, two separate mean scores for each group of animals were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Apolipoprotein E functions as a ligand for the receptor-mediated uptake of chylomicron and VLDL remnants by hepatic lipoprotein receptors (1)(2)(3). Normally, these remnant particles are rapidly removed from the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Chylomicrons and large VLDL, whose clearance is regulated by apo E, have been postulated as possible effectors. The conjunction of a reduced cholesterol absorption in e2 subjects 34 - 35 and defective apo E2 remnant uptake 36 may decrease the delivery of cholesterol to the liver. This may result in the upregulation of liver LDL receptors and accelerated fractional catabolic rates of plasma LDL in apo E3/2 subjects.…”
Section: Figure 1 Bar Graphs Of Mean Concentrations (Mg/dl) Of Totalmentioning
confidence: 99%